The the common law privilege against self-incrimination: has it been abolished - Shair Mohamad, Mohd Akram; Kamarudin, Abdul Rani (Zes Rokman Resources, 2016)
It is an inveterate principle of the common law, adopted by common law jurisdictions that any person cannot be compelled to answer any questions that may incriminate himself. This privilege against answering self-incriminating questions can only be abrogated by statute, expressly or by necessary implication. Though, this privilege has been much criticised as being obsolete, particularly in civil cases because it can prevent much relevant and strongly probative evidence from being disclosed in litigation, nevertheless, it still has a hallowed place in criminal cases. However, recent judicial decisions in Malaysia have blatantly held that this privilege against self-incrimination has gone, though the section concerned does not expressly abrogated the privilege. The purpose of this paper is to argue that in Malaysia, the privilege has not been abrogated, but is still intact.